Production and characterization of angiotensin I-converting enzyme inhibitory peptides derived from Alcalase-digested green soybean [Glycine max (L.) Merr.] proteins - Mahlid @ Hanafi, Mohammad Ariff (2018)
The prevalence of hypertension has escalated to the point where at least a quarter of the world’s adult population is afflicted and is projected to increase further. Developing and developed countries are both affected to some extent. Hypertension, by itself or in combination with several other risk factors, presents a formidable challenge to the wellbeing of modern society. However, as a lifestyle-related disease, it can be controlled via modifications to the diet. The research community has undertaken an intensive search for novel compounds able to inhibit the angiotensin Iconverting enzyme (ACE), which has been identified as a major target to control hypertension. Synthetic compounds, while effective, has given rise to undesirable sideeffects. Therefore, safer alternatives to these compounds have been sought out. ACE inhibitory peptides from food protein sources have been identified as a possible solution. Green soybean (Glycine max) has long become a popular food among East Asian countries, but is otherwise not utilized for other purposes. Green soybean has a high protein content (43.35%) which could be exploited to produce bioactive peptides, more specifically, ACE inhibitory peptides. Therefore, the work in this thesis was undertaken to investigate the potential of green soybean to generate ACE inhibitory peptides through enzymatic hydrolysis under controlled conditions. The amino acid content of green soybean was evaluated. Defatted green soybean was hydrolysed by four food-grade proteases namely, Alcalase, Papain, Flavourzyme, and Bromelain, and their hydrolysates’ ACE inhibitory activities were compared. The hydrolysate obtained using Alcalase had the strongest inhibitory activity (IC50: 0.14 mg/mL at 6 h hydrolysis time) followed by Papain (IC50: 0.20 mg/mL at 5 h hydrolysis time), Bromelain (IC50: 0.36 mg/mL at 6 h hydrolysis time), and Flavourzyme (IC50: 1.14 mg/mL at 6 h hydrolysis time) hydrolysates. Alcalase-digested hydrolysates were fractionated based on their hydrophobicity using RP-HPLC, and isoelectric points using isoelectric point focusing technique. The most effective fractions with regards to ACE inhibition were subjected to tandem mass spectrometry for peptide identification. A total of 10 peptides were identified, with five of the peptides being chosen for further characterization based on their ACE inhibitory activities; EAQRLLF, PSLRSYLAE, PDRSIHGRQLAE, FITAFR, and RGQVLS, with IC50 values of 878 μM, 532 μM, 1552 μM, 1342 μM, and 993 μM, respectively. The inhibition kinetics of these peptides was studied and a combination of competitive and uncompetitive inhibition modes was found. The results revealed that hydrolysates and peptides with ACE inhibitory activity can be derived from green soybean and might be utilised for development of functional foods with strong antihypertensive activity.